Migration of Field Rodents due to Poison-Baiting - Pasahan, S C; Sabhlok, V P (Annals of Arid Zone, 2016)
The present information comprises the results achieved as a result of the error in control success due to migration of rodent on the deployment of a rodenticide. Murids are found to be highly mobile in the fields and their range Of migration fell between 40.0 m and 76.3 m. Single exposure of Bromadiolone/Brodifacoum has kept the anticoagulants at an edge over in rodent control levels. Migration in rodents has been found occurring as a consequence of the communication brought about by the victimised animals.